Hi

Solving leaving the answer in term ofeor ln

(5^3+x) = (20^x-3)

ln 5 (3 + x) = ln 20 (x - 3)

3 ln5 + x ln5 = x ln20 - 3 ln20

3 ln5 + 3 ln20 = x(ln20 - ln5)

can it be simplified more?

Printable View

- July 29th 2010, 07:06 AMdanielh9103Can it be simplified more?
Hi

Solving leaving the answer in term of*e*or ln

(5^3+x) = (20^x-3)

ln 5 (3 + x) = ln 20 (x - 3)

3 ln5 + x ln5 = x ln20 - 3 ln20

3 ln5 + 3 ln20 = x(ln20 - ln5)

can it be simplified more? - July 29th 2010, 07:16 AMAlso sprach Zarathustra
ln(20)=ln(4*5)=ln(4)+ln(5)=ln(2^2)+ln(5)=2ln2+ln(5 )

- July 29th 2010, 07:21 AMeumyang